2013
DOI: 10.1016/j.cub.2013.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Vervet Monkeys Solve a Multiplayer “Forbidden Circle Game” by Queuing to Learn Restraint

Abstract: In social dilemmas, the ability of individuals to coordinate their actions is crucial to reach group optima. Unless exacted by power or force, coordination in humans relies on a common understanding of the problem, which is greatly facilitated by communication. The lack of means of consultation about the nature of the problem and how to solve it may explain why multiagent coordination in nonhuman vertebrates has commonly been observed only when multiple individuals react instantaneously to a single stimulus, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…We also need studies that can select producers and users with suboptimal characteristics, for example a high-ranking individual with a lower-than-expected network centrality compared to a low-ranking individual with a higher-than-expected network centrality, or a lower-ranking individual with a higher-than-expected boldness profile compared to a high-ranking individual with a lower-than-expected boldness profile. For instance, in several groups of vervet monkeys tested in an experimentally induced coordination problem, dominant individuals naïve to a foraging task learnt to wait outside of an imaginary forbidden circle that the proficient but low-ranking individual approached and solved the task and allowed food access to the whole group ( Fruteau et al, 2013 ). What is also needed is the assessment of the effects of individual characteristics on diffusion in naturally or spontaneously occurring innovations, observed from their birth to their establishment or disappearance, in a population where individuals are identifiable and their characteristics a priori known [e.g., dental flossing ( Leca et al, 2010 ) and louse egg-removal techniques ( Tanaka, 1998 ) in Japanese macaques, lobtail feeding in humpback whales ( Weinrich et al, 1992 ; Allen et al, 2013 ), or moss-sponging in chimpanzees ( Hobaiter et al, 2014 )].…”
Section: Further Perspectives On Social Diffusion Studiesmentioning
confidence: 99%
“…We also need studies that can select producers and users with suboptimal characteristics, for example a high-ranking individual with a lower-than-expected network centrality compared to a low-ranking individual with a higher-than-expected network centrality, or a lower-ranking individual with a higher-than-expected boldness profile compared to a high-ranking individual with a lower-than-expected boldness profile. For instance, in several groups of vervet monkeys tested in an experimentally induced coordination problem, dominant individuals naïve to a foraging task learnt to wait outside of an imaginary forbidden circle that the proficient but low-ranking individual approached and solved the task and allowed food access to the whole group ( Fruteau et al, 2013 ). What is also needed is the assessment of the effects of individual characteristics on diffusion in naturally or spontaneously occurring innovations, observed from their birth to their establishment or disappearance, in a population where individuals are identifiable and their characteristics a priori known [e.g., dental flossing ( Leca et al, 2010 ) and louse egg-removal techniques ( Tanaka, 1998 ) in Japanese macaques, lobtail feeding in humpback whales ( Weinrich et al, 1992 ; Allen et al, 2013 ), or moss-sponging in chimpanzees ( Hobaiter et al, 2014 )].…”
Section: Further Perspectives On Social Diffusion Studiesmentioning
confidence: 99%
“…Ostrom [ 5 ] states that individuals tend to lose their ability for coordination in social dilemmas unless they are facilitated through communications and monitoring. Interestingly, however, Fruteau et al [ 6 ] have shown that animals such as vervet monkeys overcome social dilemmas without any intervention. It thus remains an open question whether or not humans have coordination abilities to solve the dilemma to sustainably manage CPRs.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, experimental studies on factors modulating tolerance between individuals are relatively rare (Fruteau et al, 2013; Noe, 2006; Van Schaik and Carel, 2003). This is surprising given the importance of tolerance for advanced social behaviours such as social learning, cultural information, transmission and cooperation (Coussi-Korbel and Fragaszy, 1995; Noe, 2006; Bergmueller and Taborsky, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Primates and rats ( Rattus norvegicus ) are affected by others’ propensity to share food in cooperation experiments (De Waal, 2000; Hauser et al, 2003; Rutte and Taborsky, 2008; Werdenich and Huber, 2002) and, when given the choice, select tolerant partners (De Waal, 2000; Melis et al, 2006b). Longtailed macaques ( Macaca fascicularis ) and vervet monkeys ( Cercopithecus aethipos ) even change their grooming pattern towards group members who have become skilled in a foraging task, suggesting that they proactively try to affect the tolerance at feeding times of these particular individuals (Seyfarth and Cheney, 1984; Stammbach, 1988; Fruteau et al, 2013). In certain species, tolerance does not seem to be a fixed attribute, but is rather given or withheld, depending on the opponent as well as on the situation (Noe, 2006).…”
Section: Introductionmentioning
confidence: 99%